2018
DOI: 10.1007/s00429-018-1749-3
|View full text |Cite
|
Sign up to set email alerts
|

Striosome-based map of the mouse striatum that is conformable to both cortical afferent topography and uneven distributions of dopamine D1 and D2 receptor-expressing cells

Abstract: The striatum is critically involved in execution of appropriate behaviors, but its internal structures remain unmapped due to its unique structural organization, leading to ambiguity when interpreting heterogeneous properties of striatal neurons that differ by location. We focused on site-specific diversity of striosomes/matrix compartmentalization to draw the striatum map. Five types of striosomes were discriminated according to diverse immunoreactivities for the µ-opioid receptor, substance P (SP) and enkeph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
84
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 55 publications
9
84
1
Order By: Relevance
“…Supporting this observation, single-cell tracing studies of striosome SPNs have reported higher percentages of neurons with axonal projections to basal ganglia output structures than to intermediate nuclei (Fujiyama et al, 2011;Levesque & Parent, 2005). Indeed, SP-rich striosomes (which are primarily found in the medial striatum in rodents) may contain up to 70% dSPNs, but the percentage of dSPNs is far lower (as low as 40%) in other striosome regions (Miyamoto et al, 2018). This dogma, however, should be qualified.…”
Section: E Ti Ology Of S Triatal Compartmental Org Aniz Ationmentioning
confidence: 89%
See 4 more Smart Citations
“…Supporting this observation, single-cell tracing studies of striosome SPNs have reported higher percentages of neurons with axonal projections to basal ganglia output structures than to intermediate nuclei (Fujiyama et al, 2011;Levesque & Parent, 2005). Indeed, SP-rich striosomes (which are primarily found in the medial striatum in rodents) may contain up to 70% dSPNs, but the percentage of dSPNs is far lower (as low as 40%) in other striosome regions (Miyamoto et al, 2018). This dogma, however, should be qualified.…”
Section: E Ti Ology Of S Triatal Compartmental Org Aniz Ationmentioning
confidence: 89%
“…For example, acetylcholinesterase-poor regions (striosomes/patches) also express high levels of the µ-opioid receptor (MOR), while acetylcholinesterase-rich regions (matrix) express high levels of the Ca 2+ -binding protein calbindin (Herkenham & Pert, 1981;Pert et al, 1976). In general, the relative expression of dSPN-specific proteins is higher in striosomes and iSPN-specific proteins are higher in the matrix (Fujiyama et al, 2011;Guttenberg, Klop, Minami, Satoh, & Voorn, 1996;Levesque & Parent, 2005;Miyamoto et al, 2018). In general, the relative expression of dSPN-specific proteins is higher in striosomes and iSPN-specific proteins are higher in the matrix (Fujiyama et al, 2011;Guttenberg, Klop, Minami, Satoh, & Voorn, 1996;Levesque & Parent, 2005;Miyamoto et al, 2018).…”
Section: E Ti Ology Of S Triatal Compartmental Org Aniz Ationmentioning
confidence: 99%
See 3 more Smart Citations